Web-based exercise machine customization and simulation - Zhou, Y.; Zou, X.; Luo, L.; Lu, J.; Li, Z. (International Journal of Sports Science and Engineering, 2007)
A frame of the Web-based exercise machine customization and simulation system is proposed first, and the flow of work of the system is analyzed. Then the paper adopts the modeling technology Pro/E and Virtual Reality technology as the three-dimensional display technology to realize the online customization according to customers` taste, embeds Agent design system into the performance function of Virtual Machine to realize the three-dimensional dynamic simulation based on variable and real-time interaction, and proposes an user-based mathematical model for preference entropy to solve the multi-attribute decision problems with uncertain information and satisfy the design preference of users. The development of the system platform provides a new way, means and platform for meeting customers` small lot, great varieties and high quality needs. The system which is already used in some enterprises, has improved their core competencies and efficiency.